Synthesis of Stable Tetraethylenepentamine-Functionalized Mesocellular Silica Foams for CO2 Adsorption - Shou-Heng Liu; Wei-Che Hsiao; Chia-Chin Chiang (Journal of Chemistry, 2013)
Various amounts of tetraethylenepentamine (TEPA) loading on mesocellular silica foams (TEPA-MSF-x) were fabricated via a chemical grafting method in this study. The performance of dry 15%   adsorption on the TEPA-MSF-x was tested by a microbalance at 348 K under ambient pressure. Experimentally, adsorption capacities of the TEPA-MSF-x sorbents were found to be 28.5–66.7 mg /g-sorbent. In addition, TEPA-MSF-x sorbents exhibited enhanced durability during repeated adsorption-desorption cycles compared to the conventional sorbents prepared by a physical impregnation method. This significant enhancement in the stability of adsorption-desorption process was most likely due to the decreased leaching of TEPA which is covalently tethered to the surface of MSF.